IMPLIKASI PERNIKAHAN USIA DINI TERHADAP KELANGSUNGAN KEHIDUPAN RUMAH TANGGA DI KABUPATEN OGAN KOMERING ILIR (PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM) - Rian Purnama Suci (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2021)
Provisions regarding the minimum age limit for carrying out marriage are contained in Article 7 paragraph (1) of Law Number 1 of 1974 as amended by Law of the Republic of Indonesia Number 16 of 2019 which states that